2009
DOI: 10.1111/j.1399-5448.2009.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus in children and adolescents is still a rare disease in Germany: a population-based assessment of the prevalence of type 2 diabetes and MODY in patients aged 0-20 years

Abstract: The prevalence of T2DM and MODY is considerably lower than the prevalence of type 1 diabetes. Type 2 diabetes thus continues to be a rare disease in children and adolescents in Germany, as is also the case in other European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 11 publications
1
42
0
8
Order By: Relevance
“…Although the Princeton study recently showed that undiagnosed type 2 diabetes is very uncommon in adolescents and that this has not changed over the last decades [49], the findings from the Princeton study probably cannot be extrapolated to countries in which patients have only limited access to healthcare and/or the healthcare system has a suboptimal quality. Second, the quality of detection and classification of type 2 diabetes might differ between healthcare providers [29,32,35,36]. The Netherlands (1998) [37] Turkey, Ankara (not specified) [18] UK (2000) [27] UK (1998) [41]Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Princeton study recently showed that undiagnosed type 2 diabetes is very uncommon in adolescents and that this has not changed over the last decades [49], the findings from the Princeton study probably cannot be extrapolated to countries in which patients have only limited access to healthcare and/or the healthcare system has a suboptimal quality. Second, the quality of detection and classification of type 2 diabetes might differ between healthcare providers [29,32,35,36]. The Netherlands (1998) [37] Turkey, Ankara (not specified) [18] UK (2000) [27] UK (1998) [41]Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of populationbased childhood diabetes registries in Norway, Poland and Germany estimated the minimum prevalence of monogenic diabetes as 3.1/100 000 in Norwegian children, 14 4.2-4.6/100 000 in Polish children, 15 2.39/100 000 in German children 16 and 2.1/100 000 in American children. 17 The frequency of the different genetic subtypes is variable and greatly depends on the clinical recruitment (either paediatric or adult) and on the geographic origin of tested patients.…”
Section: Analytical Validationmentioning
confidence: 99%
“…The minimum prevalence of MODY was reported to be 1.1-4.2% of patients with diabetes or 2.4-4.6 cases per 100,000 [9][10][11][12][13][14][15][16]. In Russian population the frequency of MODY 2 and MODY 3 possibly are the same unlike in other countries [17].…”
Section: Mody Incidence and Prevalencementioning
confidence: 99%